Assessing the quality of life of asthmatic children using the PedQL™ - Yulia Wigoeno; Rini Sekartini; Darmawan Budi Setyanto; Sri Rezeki Hadinegoro (Indonesian Pediatric Society, 2011)
Background Asthma is the most common chronic respiratory illness in childhood. Its prevalence in Indonesia is 6.7 - 10%. Asthma influences growth, development and quality of life in affected children. Studies abroad have shown that children with asthma have a decreased quality of life (QoL), yet such data is limited in Indonesia.Objective To assess quality of life of asthmatic children in Indonesia, the influence of sociodemographic and medical characteristics on QoL, and to compare child self-reporting to their parents’ proxy-reporting.Methods This descriptive analysis, cross-sectional study was conducted from May to July 2010. We assessed the quality of life of asthmatic children aged 2-18 years using the PedsQLTM 4.0 generic scale.Results A total of 100 asthmatic children and their parents were included, with 43% of the subjects aged 8-12 years and a male to female ratio of 1.7:1. We observed that 26.8% of children who self-reported had impaired QoL, while 35% of children who reported by proxy had impaired QoL. In a multivariate analysis, we found the following characteristics to independently influence QoL: male gender (P 0.018 OR 0.26 95% CI 0.08 to 0.9) based on child self-report, and having partly controlled/uncontrolled asthma based on self-report and proxy-report (P 0.013 OR 6.24 95% CI 1.48 to 26.37 and P 0.018 OR 3.43 95% CI 1.24 to 10.05, respectively). There was good correlation between the self-report and the proxy-report on emotional and social functioning (r > 0.5), yet we found physical and school functioning to be weakly correlated (r < 0.5).Conclusions We observed a relatively high (26.8-35%) impaired QoL in asthmatic patients. Parental assessment of their child’s QoL was generally lower than the child’s self-assessment. Male gender is a protective factor against impaired QoL, but having partly controlled/uncontrolled asthma is a risk factor for lower QoL. [Paediatr Indones. 2011;51:245-51].